Red tape and delayed entry - Antonio Ciccone; Elias Papaioannou (European Central Bank (ECB), 2007)
Does cutting red tape foster entrepreneurship in industries with the potential to expand? We address this question by combining the time needed to comply with government entry procedures in 45 countries with industry-level data on employment growth and growth in the number of establishments during the 1980s. Our main empirical finding is that countries where it takes less time to register new businesses have seen more entry in industries that experienced expansionary global demand and technology shifts. Our estimates take into account that proxying global industry shifts using data from only one country–or group of countries with similar entry regulations–will in general yield biased results.
Keywords: E6; F43; L16; 330; entry; entry regulation and globally expanding industries; Unternehmensgründung; Fertigungsberufe; Markteintritt; Regulierung; Theorie